Synthesis of isatins via oxone® /TBAI-mediated on-water oxidation of indoles - Khajuria, Pratiksha; Bag, Debojyoti; Sawant, Sanghapal D. (Synthesis-Stuttgart, 2025)
Isatins and their derivatives are important scaffolds in a wide range of pharmaceuticals, bioactive compounds, and functional materials. Herein we describe a new strategy for the synthesis of isatins from indoles via Oxone (R)/TBAI-mediated oxidative dearomatization of indoles in water. The strategy works well with a variety of N-protected indoles and azaindoles.
Keywords: dearomatization; indoles; isatins; Oxidation; Water